EFEKTIVITAS LAYANAN BIMBINGAN KLASIKAL BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN PENGELOLAAN WAKTU MEDIA SOSIAL SISWA KELAS VIII-C SMP NEGERI 3 MADIUN - Wijaya, Rahmawati; Novarianing Asri, Dahlia; Ika Mariana, Mega (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social media time management is an important skill that students need to develop so that social media use does not interfere with academic activities and daily life. However, based on the Student Needs Assessment (AKPD) conducted at SMP Negeri 3 Madiun, some students were found to have difficulties managing their social media usage time. This study aimed to determine the effectiveness of classical guidance services based on Problem Based Learning (PBL) in improving students’ social media time management. The study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants consisted of 31 students of class VIII-C at SMP Negeri 3 Madiun. The research instrument was a social media time management questionnaire that had met validity and reliability requirements. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and a paired sample t-test with IBM SPSS Statistics 26. The results showed that the mean score increased from 29.903 in the pretest to 34.032 in the posttest. The paired sample t-test indicated a significance value of 0.000 (p < 0.05), revealing a significant difference between pretest and posttest scores. Furthermore, the effect size analysis yielded a Cohen’s d value of 2.391, which falls into the very large effect category. Therefore, classical guidance services based on Problem Based Learning were proven effective in improving students’ social media time management.